Gene characterization of Bradyrhizobium spp. strains contrasting in biological nitrogen fixation efficiency in soybean - Medeiros, Camila de; Pereira, Gilberto Aguiar; Freitas, Janyeli Dorini Silva de; Oliveira Filho, Olavo Bilac Quaresma de; Valle, Juliana Silveira do; Linde, Giani Andrea; Paccola-Meirelles, Luzia Doretto; Colauto, Nelson Barros; Barcellos, Fernando Gomes (Semina: Ciências Agrárias, 2020)
Bacteria from genus Bradyrhizobium can establish symbiosis with soybean and supply the plant nitrogen demands via biological nitrogen fixation (BNF). This study aimed to characterize genes related to BNF efficiency in B. japonicum strains contrasting in BNF efficiency. These gene sequences were previously identified in B. japonicum (strain S370) as probably related to the BNF efficiency in soybean using a DNA subtractive technique. These genes were amplified with primers based on B. japonicum USDA110 genome. The PCR products were digested with restriction endonucleases and the RFLP products were analyzed by horizontal electrophoresis. Among the four genes, only blr3208 and blr4511 amplified for most of the strains. Neither polymorphism of the restriction profile of blr3208 and blr4511 genes nor with endonuclease for PCR-RFLP was observed. The contrasting strains had blr3208 and blr4511 genes sequenced and the multiple alignment analysis of nucleotide sequences showed the presence of preserved internal regions, confirming the analysis with PCR-RFLP. The blr3208 and blr4511 genes are highly conserved among B. japonicum strains, which may be related to adaptive function during the evolutionary process of Bradyrhizobium genus.